New Insights Into Crustal Deformation of the Indonesia–Australia–New Guinea Collision Zone From a Broad‐Scale Kinematic Model. Issue 2 (17th February 2023) - Zhao, Siyuan; McClusky, Simon; Cummins, Phil R.; Miller, Meghan S.; Nugroho, Hendro
Abstract: The Indonesia‐Australia‐New Guinea collision zone comprises a complex system of tectonic blocks whose relative motion accommodates convergence of the Sunda Block, Pacific, Australian, and Philippine Sea plates. Previous studies have considered either the western or eastern ends of this system, in eastern Indonesia and Papua New Guinea, respectively. However, these studies had limited ability to characterize either the kinematics of the central part of the system or transitions in tectonic regime across it. In this study, we perform a simultaneous inversion of 492 earthquake slip vectors and 267 GPS velocities to quantify the block movement spanning the Sunda‐Banda Arc, Western New Guinea, and Papua New Guinea. Our best‐fitting kinematic block model comprises 23 elastic blocks, for which we estimate the rotation rates and block boundary slip rates. We show how the Cenderawasih Bay sphenochasm was likely formed by a combination of both rotations (2.82 ± 0.11°/Myr anticlockwise) of the Bird's Head Block and southwest‐directed convergence (39.9 ± 1.7 mm/yr) along the Lowlands fault. Our estimated relative slip vectors across the New Guinea Fold‐and‐Thrust Belt indicate a transition in the tectonic regime of the block boundary from predominately thrust faulting at its western segment, with a convergence rate up to 19.5 ± 0.6 mm/yr, to predominately sinistral motion in the center segment with slip rate ∼7 mm/yr, and returning to thrust in the eastern segment with a convergence rate up to 9.0 ± 0.5 mm/yr, implying the combined effect of multiple driving mechanisms. Plain Language Summary: The Indonesia–Australia–New Guinea collision zone is an east‐west elongated belt of complex tectonics at the northern edge of the Australian Plate, where the northward movement of the Australian continental lithosphere is accommodated by relative movement among a series of "microplates" in Indonesia and New Guinea. The interactions among these plates span the full gamut of tectonic phenomena. In this study, we use GPS measurements of crustal motion and earthquake data to estimate the motion of the tectonic units (plates and microplates) within the collision zone. While previous studies have considered either the western or eastern parts of this collision zone in isolation, in this study we consider together all the blocks spanning the zone from west to east. We show that this provides greater insight into changes in the tectonic regime through the center of the collision zone, and allows us to establish a new model for the development of the Cenderewasih Embayment in north‐central New Guinea. Key Points: A new broad‐scale kinematic model has been developed spanning the 5, 000 km length of the Indonesia‐Australia‐New Guinea collision zone The evolution of Cenderawasih Bay is based on the joint effect of the rotation of the Bird's Head block and the WSW drift of Weyland Thrust The New Guinea Fold‐and‐Thrust Belt experiences two transitions in its tectonic regime, as it traverses the center of the collision zone